(untitled) (Pain medicine, 2017)
The article deals with the use of long-term venous access and the rationale for its use in pain medicine. It is known that, protein-energy deficiency, previous blocks of chemotherapy, previous multiple venipunctures of peripheral veins often make venous access in oncology patients impossible and lead to the development of pain syndrome. It is especially important in the systemic control of pain, when painkillers (NSAIDs, narcotic analgesics, etc.) are routinely administered intravenously. Therefore, the preventive implantation of the venous port-system is a factor that greatly facilitates the care of a palliative patient and the provision of analgesic therapy. It should be noted that the use of a port-system is provided at home, by the patient or relatives. This is the factor that facilitates the patient’s condition, reduces the duration of hospitalization, reduces the burden on medical staff. Thus, the implantation system of venous access allows adequate and stable anesthesia, chemotherapy and infusion therapy.